Does anticoagulation improve outcomes of microvascular free flap reconstruction following head and neck surgery: a systematic review and meta-analysis. Issue 10 (December 2022) - Dawoud, B.E.S.; Kent, S.; Tabbenor, O.; Markose, G.; Java, K.; Kyzas, P.
Abstract: The commonest cause of microvascular free flap failure is thrombosis at the anastomosis. Pharmacological antithrombotic therapies have been used to mitigate this risk, but they carry the risk of bleeding and haematoma formation. To justify any intervention, it is necessary to evaluate the benefits and balance of risks. This meta-analysis aims to quantify the value of systemic anticoagulation during head and neck free tissue reconstruction. We performed a systematic review on the impact of additional prophylactic antithrombotic therapy on head and neck (H&N) free tissue transfer (on top and above the use of low molecular weight heparin to prevent deep vein thrombosis). We carried a PRISMA-guided literature review, following registration with PROSPERO. All studies analysing the possible impact of prophylactic anticoagulants on free flap surgery in the head and neck were eligible. The primary outcome was perioperative free flap complications (perioperative thrombosis, partial or total free flap failure, thrombo-embolic events, or re-exploration of anastomosis). Secondary outcomes included haematoma formation or bleeding complications requiring further intervention. We identified eight eligible studies out of 454. These included 3531 free flaps for H&N reconstruction. None of the assessed interventions demonstrated a statistically significant improvement in free flap outcomes. Accumulative analysis of all anti-coagulated groups demonstrated an increased relative risk of free flap complications [RR 1.54 (0.73–3.23)] compared to control albeit not statistically significant (p = 0.25). Pooled analysis from the included studies showed that the prophylactic use of therapeutic doses of anticoagulants significantly (p = 0.003) increased the risk of haematoma and bleeding requiring intervention [RR 2.98 (1.47-6.07)], without reducing the risk of free flap failure. Additional anticoagulation does not reduce the incidence of free flap thrombosis and failure. Unfractionated heparin (UFH) consistently increased the risk of free flap complications. The use of additional anticoagulation as 'prophylaxis' in the perioperative setting, increases the risk of haematoma and bleeding.